Study the molecule species of phosphatidylethanolamine class in soft coral \(Sinularia flexibilis\) lipid at different times of the year - Dang Thi , Phuong Ly; Pham Minh , Quan; Nguyen Thi, Nga; Trinh Thi , Thu Huong; Andrey Imbs, Borisovich (Vietnam Journal of Marine Science and Technology, 2021)
Samples of soft coral Sinularia flexibilis were collected in February, May, August, November in Nha Trang, Khanh Hoa. The content of molecular species in phosphatidylethanolamine class in the lipid of obtained coral samples has been determined. Identified 14 types of PE molecule species, in which the alkenylacyl PE 18:1e/20:4 has the highest concentration, ranging from 51.35% to 63.16% in 4 samples, the highest and lowest concentrations were in a sample collected in August and November, respectively. Samples collected in August and May have a lower diacyl PE ratio than samples collected in November and February. This study identified the lowest alkylacyl and the highest alkenylacyl concentration in a sample collected in August. The fatty acids present in this class are 17:1, 18:1, 18:2, 19:1, 20:4, and 24:5. The percentage of the total content of molecule species by each fatty acid is similar between months. The total content of molecule species containing 20:4n fatty acids was 80.08–84.27% of the PE class, and the difference was not significant in 4 coral samples. There was an inverse correlation between the total content of molecule species containing 20:4n PUFA and the total content of 20:4n fatty acid and the proportional correlation between the content of PE molecule species containing 24:5n PUFA content of 24:5n fatty acid in total fatty acids.